Effects of Learning Log on the Statistics Performance of College Students - Lines, Cainne Dorothy (Journal of Interdisciplinary Perspectives, 2025)
This experimental study evaluated the effects of learning logs as a formative assessment of the performance of the statistics. The study addressed the gap in research on effective formative assessments in statistical education. This was made through a pretest-post-test comparison of the performance before and after the intervention. The study took place in the College of Teacher Education in one of the state universities in Cebu. The findings showed that the pretest performance of the experimental group, which was subjected to a learning log, and the control group, which was subjected to conventional formative assessment, were Below Passing and did not meet the passing percentage set by the university. In the post- test, the students in the control group showed Below Passing while the students in the experimental group performed Above Passing. Statistical analysis revealed a significant improvement in the mean scores for both groups, with the experimental group showing a greater mean gain. According to the findings, learning logs helped students perform better in Statistics. These findings suggest that learning logs can enhance students' performance in Statistics. Further research is recommended to explore this intervention in greater depth over a longer period.